Métodos analíticos aplicados ao estudo de pessoas com deficiência - Daga, Silvio Luis (2018)
The Global education indicators show that Brazil needs action to improve its current undesirable position. In an intrinsic way to the problem of education also encompasses people who have some kind of special need. To this public is perceived by the data of the Brazilian Institute of Geography and Statistics (IBGE) that the proportion of this population is significant and that is not perceived in public policies of the government some type of movement to include these students that in the majority of the cases depend on a differentiated environment or even specific classroom methodologies. Given this context, the objective of this work is the one that consists of a methodological proposal of analytical methods to translate the open and public data in educational, social and economic analysis, allowing the discovery of strategic information for managers who deal with deficient students, as is the case of the Association of Parents and Friends of the Exceptional (APAE). The work has as contributions a Multidimensional Modeling that allows to present different strategic responses of the special education in terms of data visualization and also the use Clustering through the K-Means algorithm that also allows discovery from non-trivial knowledge to raw data analyzes. The results have been extensively explored using Data Visualization methods and are important, among other things, for defining public policies for people with special needs.